Exploring the Drivers of Halal Certification Adoption in Depok City’s MSMEs for Sustainable Economic Empowerment - Fadhli Suko Wiryanto; Muhammad Anwar Fathoni; Diva Azka Karimah (El-Barka Journal of Islamic Economics and Business, 2025)
Indonesia has achieved positive results in the world halal food sector in the SGIER, that Indonesia can compete in the global halal food, which will also have an impact on improving the sustainable economy in the halal food sector. Indonesia, through the Halal Product Guarantee Agency, implemented a mandatory halal certification program. This was implemented especially Micro, Small, and Medium Enterprises, can compete in providing halal-certified products. However, behind this achievement, it was found that the reality of halal certificate issuance in Depok have not made significant contribution to national achievements, namely only 6.05%. MSMEs as one of the pillars of the economy play a vital and significant role in contributing to state revenue. On the other hand, the Government requires halal certification for food and beverage products produced by micro, small, and medium enterprises until the deadline of October 2026. However, the proportion of MSMEs that have obtained halal certification is still relatively low when compared to the total number of MSMEs operating in Depok. This research uses a quantitative method by distributing questionnaires to respondents. Data will be processed using PLS, outer models, and inner models. The results of this study indicate that religiosity, halal literacy, and perceived benefits influence the interest in applying for halal certification. Religiosity influences interest in applying for halal certification due to the belief that selling halal products will encourage business owners to operate their businesses in accordance with religious principles. Halal literacy also influences interest in applying for halal certification among MSMEs in Depok City because a strong understanding encourages business owners to meet the needs of Muslim consumers more responsibly. Perceived benefits also play a role because halal certification serves not only as proof of halalness but also as a strategy to increase consumer loyalty.